Optimisation of microencapsulation of turmeric extract for masking flavour - Natcha Laokuldilok (2018)
© 2015 Elsevier Ltd. The aim of this study was to evaluate the odour masking property, encapsulation efficiency and physicochemical properties of turmeric extract prepared by a binary blend of wall materials, i.e. brown rice flour (BRF) and beta-cyclodextrin (β-CD). Response surface methodology was applied to investigate the effect of encapsulation processing variables, including core loading mass (5-25%) and β-CD (5-20%) concentration on product recovery, moisture content, hygroscopicity, curcuminoids encapsulation and volatile release. To investigate odour masking properties of a wall material combination, volatiles in headspace were monitored by GC-MS using ar-turmerone and 2-methyl-4-vinylguaiacol as marker compounds to represent turmeric extract. The obtained results revealed an optimal encapsulation process was 5% of core loading mass with addition 20 g/L of β-CD, since it enabled high curcuminoids encapsulation with low volatile release, moisture content and hygroscopicity. Turmeric powder with reduced odour can be used as a nutrient supplement or natural colorant for food products.